What is in our seas? Assessing anthropogenic litter on the seafloor of the central Mediterranean Sea. (November 2020) - Garofalo, G.; Quattrocchi, F.; Bono, G.; Di Lorenzo, M.; Di Maio, F.; Falsone, F.; Gancitano, V.; Geraci, M.L.; Lauria, V.; Massi, D.; Scannella, D.; Titone, A.; et al.
Abstract: Abundance, composition, and distribution of macro-litter found on the seafloor of the Strait of Sicily between 10 and 800 m depth has been studied using data collected by bottom trawl surveys MEDITS from 2015 to 2019. Three waste categories based on the items use were considered: single-use, fishing-related and generic-use. Over 600 sampling sites, just 14% of these were litter-free. The five-years average density of seafloor litter was 79.6 items/km 2 and ranged between 46.8 in 2019 and 118.1 items/km 2 in 2015. The predominant waste type was plastic (58% of all items). Regardless of material type, single-use items were a dominant (60% of items) and widespread (79% of hauls) fraction of litter with a mean density of 48.4 items/km 2 . Fishing-related items accounted for 12% of total litter items. Percentage of dirty hauls and litter density increased with depth. Analysis of the relation density-depth indicates a progressive increase of litter density beyond depth values situated within the interval 234–477 m depending on the litter category. A significant decrease in litter density by categories was observed over the period. Patterns of spatial distribution at the higher depths (200–80 0m) resulted stable over the years. Density hotspots of fishing-related items were found where the fishing activity that uses fish aggregating devices (FADs) is practised and in the proximity of rocky banks. Single-use and generic-use objects densities were greater on the seafloor along main maritime routes than other areas. Comparisons between the percentage of hauls littered with anthropic waste from the mid-1990s against those in 2018–19 highlighted an increase of about 10.8% and 15.3% for single-use items and fishing-related items respectively, and a decrease of 18.6% for generic-use items. This study provides a snapshot of the current situation of littering in the central Mediterranean Sea and represents a solid baseline against which the effectiveness of current and future mitigation strategies of the litter impact on marine environment can be measured. Graphical abstract: Image 1 Highlights: The density of seafloor macro-litter in the Strait of Sicily increases with depth. Single-use and generic-use items accumulate along shipping routes. Fishing-related items are associated with specific fishing areas. The occurrence of litter is higher than in the '90s but decreases from 2015 to 2019. Baseline information useful for mitigation policies of seafloor macro-litter. Abstract : Main findings: Higher density of litter distribution at deeper bottoms. Single-use and generic-use items accumulate along main shipping routes; fishing-related items are associated with specific fishing activities.